Influence of phenolphthalein groups on the structure and properties of poly(arylene ether sulfone nitrile)-based anion exchange membranes for fuel cells. Issue 106 (13th October 2015) - Lai, Ao Nan; Zhuo, Yi Zhi; Lin, Chen Xiao; Zhang, Qiu Gen; Zhu, Ai Mei; Ye, Mei Ling; Liu, Qing Lin
Abstract : Two series of novel poly(arylene ether sulfone nitrile) (PESN) multiblock copolymers are synthesized to prepare anion exchange membranes (AEMs) for alkaline fuel cells. Abstract : Two series of novel poly(arylene ether sulfone nitrile) (PESN) multiblock copolymers are synthesized to prepare anion exchange membranes (AEMs) for alkaline fuel cells. To study the effect of phenolphthalein groups on the structure and properties of the membranes, the ion groups facilitating the formation of ion clusters are selectively and densely located on the phenolphthalein-sulfone segments of one and on the bisphenol A-sulfone segments of the other. The morphology and structure of the membranes are observed by atomic force microscopy and small angle X-ray scattering. The phenolphthalein-containing type endows the AEMs with a much clearer and more-defined microphase-separated structure leading to the formation of much larger and more developed interconnected ion-transport channels. As a result, high hydroxide conductivity (in the range of 2.04–12.98 × 10 −2 S cm −1 from 30 to 80 °C) and H2 /O2 fuel cell performance (an open circuit voltage of 0.92 V and a maximum power density of 66.4 mW cm −2 at 60 °C) can be achieved. Furthermore, the phenolphthalein-containing AEMs also show higher water uptake and mechanical strength, lower swelling ratio, and higher thermal and alkaline stability than the phenolphthalein-free AEMs.